Current National Economy and Outlook 2022: Pandemic Impact and Recovery Projections - Sipra Barutu (MAR-Ekonomi: Jurnal Manajemen, Akuntansi Dan Rumpun Ilmu Ekonomi, 2024)
The COVID-19 pandemic has had a significant impact on the national economy, causing contractions in various sectors and changes in the dynamics of economic policy. In 2022, economic recovery is a top priority with various fiscal and monetary policies implemented to accelerate economic growth and stability. This study uses a literature review method to analyze the impact of the pandemic and projections for Indonesia's economic recovery. The results of the study show that the Indonesian economy has shown good resilience post-pandemic, with indicators such as investment, exports, and domestic consumption supporting positive growth. However, global challenges such as inflation, economic uncertainty, and commodity price fluctuations remain risks that must be anticipated. With effective policy management, sustainable economic recovery is expected to be realized, supporting inclusive growth and public welfare.